Disaster Mitigation and Human Security Study: Jayapura City Community on Earthquake Disaster Mitigation Perspectives - Melyana Ratana Pugu (CV. Ridwan Publisher, 2023)
Disaster mitigation and human security are two things that cannot be separated in relation to saving people as an important subject of the state. This paper aims to provide an in-depth analysis of the importance of disaster mitigation within the framework of human security from the perspective of international relations. The method used is a qualitative research method in which primary data is obtained through samples provided to residents via Google forms and also through secondary data, namely news, newspapers and other internet sources. The primary and secondary data obtained are then processed and get an accurate analysis to then be used as valid data. The output of this study is that so far there has been no socialization related to disaster mitigation in the city of Jayapura and most of the respondents agree that they get disaster mitigation lessons through themselves by reading and watching through television or cellphone media. In international relations, when this situation occurs, human security in this region is actually very vulnerable, so it is necessary for the government to pay attention to socializing and learning about disaster mitigation for Jayapura city residents.